La construction d’une éthique de vie à travers l’apprentissage transformationnel : la Franc-maçonnerie comme espace d’éducation au « savoir-exister » ? - Ivan Alsina (Éducation et Socialisation)
Freemasonry wants to build subjects with an increased awareness of their potential and wishing to act with implication for societal transformations. Its evolution over the centuries has shaped an ideology based historically on religious and later humanistic principles. The subjects integrating it must gradually soak up the different formal and informal learnings specific to the Masonic space in order to integrate an ideology based on a search for virtue questioning learner’s paradigms. The transformational learning is based on critical assessment and examination of assumptions through a critical reflection. Based on a qualitative research and psychometrical assessment of emotional skills, the result shows that this biographical restructuring will result in transformational modalities. The acquisition of new behaviors focus on self-knowledge, otherness recognizing are impacting the development of emotional capital and thus allow the subject to move towards the appropriation of the concept of “savoir-exister” which we are trying to expose psychosociological and organizational benefits.